Perception of consumer toward digital marketing strategy on international athleisure wear - Tan, Jian Ming (2019)
Currently, due to human interaction paradigm had shifted from face to face into the virtual, it is an opportunity for marketers to seize it but the problem is there are too many digital marketing strategy is in the globe. So in order to market product effectively and efficiently, consumer perception on those strategy are important which varies from positive or either negative in order for marketers to prevent to adopt the wrong strategy and also know how to think from the perspective of a consumer towards those digital marketing strategy. By doing so will not only benefit marketers but also for consumer in the manner of extracting the strategy that will make consumer finds interest in and also an added value things to them by increasing their quality of internet browsing activity. In this research thesis, it is in qualitative method in order to know more detail of a perception and also opinion of a consumer. Interview has been done through faceto-face with the total of five participant with the general knowledge of information technology and social media. The result from them has conclude that search engine optimization are better off for search engine marketing is because minority are detest against sponsored link, behavioral targeting has improved the impression of it and in-stream video are the most effective forms of display advertising than popup ads and also banners ads, and it is important for a social media post to be more vividness, informative and also entertaining while interactivity are not so. Influencer marketing has mentioned by those participant but it is not included in this research paper so future studies can focus and select in this aspect.